Digitization of the Arabic linguistic heritage: Problems, challenges, and prospects of linguistic research - Nora, Larouane (The International tax journal, 2026)
The study aims to shed light on the importance of digitizing the Arabic linguistic heritage and its role in preserving the linguistic and cultural identity of the nation, and highlight its potential in the development of contemporary linguistic research, and the research poses a problem that: to what extent can the digitization of the Arabic linguistic heritage contribute to its preservation, revival, and activate its presence in modern linguistic studies, and what challenges hinder its transition to a digital environment. The study also reviews the technical, methodological and cultural challenges facing digitization projects, such as the diversity of Arabic fonts, the lack of human expertise, and the absence of unified standards, highlighting Arab and international experiences and lessons learned from them, in order to provide a clear scientific vision for the development of digitization projects of Arab heritage to serve scientific research and education.